Entanglement swelling in polymer glasses: Chain length dependence on participation in network events - McGraw, Joshua (My University, 2008)
When a polymer system is strained below its glass transition temperature, T9 , deformed regions called crazes may be formed that have a characteristic extension ratio, λ. Examining the regions of deformed material, which are almost visible to the naked eye, and measuring λ with the use of atomic force microscopy gives information about the space between entanglements along a polymer chain, which is a truly molecular quantity. In this work we present the results of experiments in which entanglements in high molecular weight polystyrene (PS) samples have effectively been swelled by diluting the network with low molecular weight PS. We find that these experiments not only tell us how the molecular weight of a polymer can affect its contribution to the polymer network, but also give an entirely new method of determining the entanglement molecular weight, Me, of a polymer system.
Keywords: Entanglement swelling; polymer glasses; Chain length; network events